The reproductive cycle of the male sleep snake Sibynomorphus mikanii (Schlegel, 1837) from southeastern brazil - Rojas, Claudio A.; Barros, Verônica A. [UNESP]; Almeida-Santos, Selma M. [UNESP] (Wiley, 2013)
This study describes the male reproductive cycle of Sibynomorphus mikanii from southeastern Brazil considering macroscopic and microscopic variables. Spermatogenesis occurs during spring-summer (September-December) and spermiogenesis or maturation occurs in summer (December-February). The length and width of the kidney, the tubular diameter, and the epithelium height of the sexual segment of the kidney (SSK) are larger in summer-autumn (December-May). Histochemical reaction of the SSK [periodic acid-Schiff (PAS) and bromophenol blue (BB)] shows stronger results during summer-autumn, indicating an increase in the secretory activity of the granules. Testicular regression is observed in autumn and early winter (March-June) when a peak in the width of the ductus deferens occurs. The distal ductus deferens as well as the ampulla ductus deferentis exhibit secretory activities with positive reaction for PAS and BB. These results suggest that this secretion may nourish the spermatozoa while they are being stored in the ductus deferens. The increase in the Leydig cell nuclear diameter in association with SSK hypertrophy and the presence of sperm in the female indicate that the mating season occurs in autumn when testes begin to decrease their activity. The peak activity of Leydig cells and SSK exhibits an associated pattern with the mating season. However, spermatogenesis is dissociated of the copulation characterizing a complex reproductive cycle. At the individual level, S. mikanii males present a continuous cyclical reproductive pattern in the testes and kidneys (SSK), whereas at the populational level the reproductive pattern may be classified as seasonal semisynchronous. © 2012 Wiley Periodicals, Inc.
Keywords: Ampulla ductus deferentis; Mating; Neotropical Colubridae; Sexual segment of the kidney; Spermatogenesis; animal; Brazil; Colubridae; cytology; cytoplasm; histology; kidney; Leydig cell; male; male genital system; organ size; reproduction; season; spermatogenesis; spermatozoon; testis; ultrastructure; vas deferens; Animals; Cytoplasm; Genitalia, Male; Kidney; Leydig Cells; Male; Organ Size; Reproduction; Seasons; Spermatozoa; Testis; Vas Deferens